Response surface optimized extraction of triterpenoids from red Vietnamese Ganoderma lucidum and anticancer evaluation of the extract - Thuy Linh, Ngo Thi; Dat, Tran Do; Tai, Nguyen Tan; Linh, Nguyen Thi; Thao My, Phan Le; Kim Ngan, Nguyen Thi; Anh, Nguyen Thi Van; Thanh, Vuong Hoai; Viet, Nguyen Duc; Nam, Hoang Minh; et al. (Vietnam Journal of Science and Technology, 2021)
Triterpenoids are considered to be the major pharmaceutical active compounds found in the macrofungus Ganoderma lucidum (G. lucidum). Extraction conditions of triterpenoids from the Vietnamese red G. lucidum were optimized by response surface methodology using ultrasound –assisted extraction (UAE) method. A Box – Behnken experimental design was used to determine the simultaneous influences of three independent variables, namely solvent-to-material ratio, extraction time, and ultrasonic power on the yield of triterpenoids. The highest yield of triterpenoids obtained under optimum conditions including extraction time of 55 min, ultrasonic power of 480 W, solvent-to-material ratio of 27:1 mL/g was 9.5768 ± 0.228 mg/g according to ultraviolet-visible spectroscopy (UV-Vis) analysis. Besides, the hot water extraction method was carried out in order to compare with UAE in terms of the yield of triterpenoids. The results of anticancer evaluation of the extract obtained indicated that with the half-maximal inhibitory concentration value of 67.25 ± 0.82 µg/mL on the human Hep-G2 liver cancer cell lines, triterpenoids extracted from G. lucidum could be regarded as a potential agent for medicinal treatment.